ANALISIS PENGARUH STORE ENVIRONMENT DAN BRAND IMAGE TERHADAP IMPULSE BUYING PADA DELTA DEWATA SUPERMARKET - Wulansari, Ni Putu Rahayu; Seminari, Ni Ketut (E-Jurnal Manajemen; Vol 4 No 9 (2015), 2015)
This research was conducted at Ubud, Gianyar Bali Supermarket Bali. Sample size of 85 customers who make purchases at the Delta Dewata Supermarket at least twice the minimum age of 17 years. The sampling technique used in this research is purposive sampling. Data was collected through questionnaire that uses 5-point Likert scale to measure the 17 indicators. The analysis technique used is multiple linear regression analysis, simultaneous test, test and test partial dominant influence. The results showed that strore environment partially positive and significant impact on impulse buying in Delta Dewata Supermarket. Second, the brand image is partially positive and significant impact on impulse buying in Delta Dewata Supermarket. Third, the dominant influence of variables in the dependent variable is a variable with a value brand image Standardized Beta Coefficients of 0,447.
Keywords: impulse buying, store environment, brand image